2018
DOI: 10.1021/acs.jafc.8b04665
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti Galectin Competes with Cry11Aa for Binding to ALP1 To Modulate Cry Toxicity

Abstract: The key step for the toxicity of Bacillus thuringiensis subsp. israelensis (Bti) is the interaction between toxins and putative receptors; thus, many studies focus on identification of new toxin receptors and engineering of toxins with higher affinity/specificity for receptors. In the larvae of Aedes aegypti, galectin-14 was one of the genes upregulated by Bti treatment. RNAi knockdown expression of galectin-14 and feeding recombinant galectin-14 -thioredoxin fusion protein significantly affected survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…However, bacteria loading was not influenced by MaGal2 knockdown, which indicated that bacteria loading does not normally occur in J IV . In addition, galectins both mediate recognition and effector function in innate immunity, and also mediate developmental processes (Rao et al ., 2016; Zhang et al ., 2018a). However, MaGal2 may also have additional roles in Monochamus beetles, and should therefore be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, bacteria loading was not influenced by MaGal2 knockdown, which indicated that bacteria loading does not normally occur in J IV . In addition, galectins both mediate recognition and effector function in innate immunity, and also mediate developmental processes (Rao et al ., 2016; Zhang et al ., 2018a). However, MaGal2 may also have additional roles in Monochamus beetles, and should therefore be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) structures of Cry1Ab1 toxic core and Cry-binding proteins were predicted by PHYRE2. GRAMM-X Protein-Protein Docking Web Server v.1.2.0 was used to predict the molecular docking of Cry1Ab1 toxic core and Cry-binding proteins, and then the docking results was analyzed and showed in the Discovery Studio 2.5 (Kang et al 2017;Zhang et al 2018). The functional domain of Crybinding proteins was acquired from the UniProt database.…”
Section: Molecular Docking and Binding Sites Analysismentioning
confidence: 99%
“…Zhao et al found that Cry41-realted interacted with Cathepsin B and enhanced its activity, causing acceleration of apoptosis of aphid cells (Zhao et al 2020). Additionally, galectin-14 was reported to compete with Cry11Aa for binding to BBMVs and ALP1 in Aedes aegypti to prevent effective binding of the toxin to receptors (Zhang et al 2018). Hence, the mechanisms for Cry toxins against insects are believed to be much more complicated than before.…”
Section: Introductionmentioning
confidence: 99%
“…Many animal lectins are glycosylated, but the galectin family seems to be an exception [55,56]. Galectins have been reported in a few insects, including D. melanogaster, A. gambiae, A. aegypti, and the sand fly Phlebotomus papatasi [57][58][59][60][61]. Galectins expressed in the insect gut have been shown to participate in the neutralization of bacterial toxins [57,58].…”
Section: Insect Lectinsmentioning
confidence: 99%